Shotgun Proteomics Identifies Active Metabolic Pathways in Bleached Coral Tissue and Intraskeletal Compartments - Axworthy, Jeremy B.; Timmins-Schiffman, Emma; Brown, Tanya; Rodrigues, Lisa J.; Nunn, Brook L.; Padilla-Gamiño, Jacqueline L. (Frontiers in Marine Science, 2022)
Coral bleaching events are increasing with such frequency and intensity that many of the world's reef-building corals are in peril. Some corals appear to be more resilient after bleaching but the mechanisms underlying their ability to recover from bleaching and persist are not fully understood. We compared the proteomes in tissue and skeleton compartments of experimentally bleached and control (i.e., non-bleached) colonies of Montipora capitata, a Hawaiian species noted for its resilience after bleaching. We identified 2361 proteins in coral tissue and skeleton for both bleached and non-bleached individuals. In bleached coral tissue, 63 proteins were significantly more abundant and 28 were significantly less abundant compared to non-bleached tissue. In bleached skeleton, 22 proteins were significantly more abundant and 17 were significantly less abundant compared to non-bleached skeleton. Gene ontology (GO) and pathway analyses revealed metabolic processes that were occurring in bleached corals but not in non-bleached corals. Bleached coral tissue used the glyoxylate cycle to derive carbon from internal storage compounds such as lipids, had a high protein turnover rate, and shifted reliance on nitrogen from ammonia to nitrogen produced from the breakdown of urea and betaine. Bleached skeleton compartmentalized the shunting of glucose to the pentose phosphate pathway. Bleached corals increased abundances of several antioxidant proteins in both the tissue and skeleton fractions compared to non-bleached corals. These results highlight contrasting strategies for responding to bleaching stress in different compartments of bleached M. capitata and shed light on some potential mechanisms behind bleaching resilience. This study, the first to use proteomics on thermally stressed, functionally different compartments of a reef-building coral, represents an important baseline for future studies on the physiological effects of bleaching on protein expression in this ecologically important coral.